1981
DOI: 10.1136/bmj.282.6267.864
|View full text |Cite
|
Sign up to set email alerts
|

Tea consumption: a cause of constipation?

Abstract: Uncontrolled clinical observations in our outpatient clinic suggested that severe constipation in young adults was related to tea consumption of one to two litres daily. We have therefore carried out a study on healthy volunteers. Subjects, methods, and resultsTwelve healthy volunteers aged [23][24][25][26][27][28][29][30] years participated in the study, which comprised two test periods of seven days. Diet decreased from 436 to 310 iLmol/24 h (p<005) during the tea period, whereas faecal mass showed only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…Tea was hypothesized to exert a constipating effect through a theophylline-mediated (a metabolite from caffeine), extracellular dehydration. 19 On the other hand, a stimulating effect of tea on GI motility has also been reported. 20 Therefore, in our study caffeinecontaining tea was excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Tea was hypothesized to exert a constipating effect through a theophylline-mediated (a metabolite from caffeine), extracellular dehydration. 19 On the other hand, a stimulating effect of tea on GI motility has also been reported. 20 Therefore, in our study caffeinecontaining tea was excluded.…”
Section: Discussionmentioning
confidence: 98%
“…In healthy volunteers a large amount of tea (four bags in 2 l daily for 1 week) slowed colon transit [25]. The authors speculated that theophylline may by its diuretic effect dehydrate the volunteers, thus increasing water extraction from the stools.…”
Section: Discussionmentioning
confidence: 98%
“…However, in some countries including the UK, tea is drunk as black tea with milk added, and the present study was designed to test the hypothesis that black tea as commonly consumed might alter blood cholesterol levels and another cardiovascular disease risk factor, blood pressure. A Danish study has also suggested that severe constipation was related to the daily tea consumption of 1 or 2 litres (Hojgaard et al 1981), so the opportunity was taken to observe changes in bowel habit. Sixty-five subjects took part in a 10-week crossover study comparing the drinking of six or more mugs of black tea daily with a placebo in two 4-week periods, after a 2-week run-in period.…”
mentioning
confidence: 99%